Effective Tax Administration and Institutionalization of Accounting Systems in Small and Medium Scale Enterprises: Evidence from Nigeria - Stanley, Ogoun (Journal of Empirical Studies, 2014)
The study investigated the role of effective tax administration in institutionalizing accounting systems in Small and Medium Scale Enterprises (SMEs) in Nigeria against the backdrop of the prevalence of poor accounting systems in this sector. Data was obtained from SME operators and staff of the internal revenue agencies like the Federal Inland Revenue Service (FIRS) and State Boards of Internal Revenue (SBIRs) as applicable in Nigeria. The econometric e-view was used to analyze the data so obtained, and it was observed that the lack of an effective tax administrative system which undermines the collection of profit tax from the operators of this sector accounts to a large extent for the non institutionalization of accounting systems SMEs in Nigeria. The study also identified several variables that militate against the establishment of an effective tax administrative system in the country. Accordingly the study advocated the need to build strong institutions, enact appropriate laws and implement stiffer penalties for defaulters. This should be predicated on the basis of an enhanced citizens’ confidence in the government and its institutions, which can be attained through the enthronement of fiscal transparency and accountability framework and good governance that has the capacity for building trust thereby enhancing voluntary compliance with tax laws.